Pengaruh Social Media Marketing dan Influencer Marketing Terhadap Brand Awareness Produk Somethinc Di Tanjungpinang - Haryani, Dwi Septi; Nurul Sultania; Ratnasari, Sri Langgeng; Elvira, Mita; Fenny; Fauzar, Selvi (Program Studi Manajemen FEBM UMRAH, 2026)
This study aims to examine the effect of social media marketing and influencer marketing on brand awareness of Somethinc products in Tanjungpinang. The research employs a quantitative method using a survey approach. The study population consists of followers of Somethinc’s TikTok account, with a sample of 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that, partially, social media marketing has a positive and significant effect on brand awareness of Somethinc products, with a tvalue of 4.197 and a significance level of < 0.001. Influencer marketing also shows a positive and significant effect on brand awareness, with a tvalue of 3.314 and a significance level of 0.001. Furthermore, the simultaneous test (F-test) reveals that social media marketing and influencer marketing jointly have a significant effect on brand awareness, with an Fvalue of 38.145 and a significance level of < 0.001. In conclusion, digital marketing strategies through TikTok social media and collaborations with credible influencers are effective in enhancing brand awareness of Somethinc products in Tanjungpinang.